2010
DOI: 10.1111/j.1348-0421.2010.00230.x
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia pseudomallei RpoS regulates OxyR and the katG-dpsA operon under conditions of oxidative stress

Abstract: Burkholderia pseudomallei, the causative agent of the potentially fatal tropical disease melioidosis, is known to be highly resistant to oxidative stress although the mechanism of this resistance remains to be fully elucidated. Previous studies have shown that an OxyR is involved in the regulation of oxidative stress via the katG and dpsA genes encoding KatG and DpsA and that the alternative sigma factor, RpoS, plays a critical role in resistance to oxidative stress by regulating katG and katE genes. Here it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…The heme containing Bfr is maximally expressed when Fe is abundant and accounts for the majority of stored Fe (109). While inactivation of bfr elevates the intracellular free Fe concentration and enhances susceptibility to H 2 O 2 stress, the DNA-binding protein Dps provides protection from oxidative damage without affecting the steady-state intracellular free Fe concentration, and it is also known to be induced during oxidative stress in Burkholderia pseudomallei, thereby protecting this pathogen from organic hydroperoxides and aiding its intramacrophage survival (110,111). Taken together, the reduced expression of several genes involved in resistance of Salmonella to osmotic and oxidative stresses and iron-limiting conditions correlates with the impaired survival of LP strains under oxidative and acidic stress as well as reduced intramacrophage survival (18).…”
Section: Resultsmentioning
confidence: 99%
“…The heme containing Bfr is maximally expressed when Fe is abundant and accounts for the majority of stored Fe (109). While inactivation of bfr elevates the intracellular free Fe concentration and enhances susceptibility to H 2 O 2 stress, the DNA-binding protein Dps provides protection from oxidative damage without affecting the steady-state intracellular free Fe concentration, and it is also known to be induced during oxidative stress in Burkholderia pseudomallei, thereby protecting this pathogen from organic hydroperoxides and aiding its intramacrophage survival (110,111). Taken together, the reduced expression of several genes involved in resistance of Salmonella to osmotic and oxidative stresses and iron-limiting conditions correlates with the impaired survival of LP strains under oxidative and acidic stress as well as reduced intramacrophage survival (18).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to providing protection against oxidative stress, AhpC also helps B. pseudomallei to evade killing by RNI [96]. Expression of these genes ( katG , dpsA and ahpC ) was shown to be dependent on the global regulator OxyR, and consistent with this, B. pseudomallei oxyR mutants were hypersensitive to H 2 O 2 [95-98]. …”
Section: Intracellular Survivalmentioning
confidence: 95%
“…Earlier studies of RpoS regulated proteins in B. pseudomallei have shown that the RpoS sigma factor plays a key role in stress response systems . In addition, it has been demonstrated that OxyR and DpsA, proteins involved in oxidative stress response, are regulatory target of RpoS . Here, a global approach was utilized to explore other B. pseudomallei proteins that respond to oxidative stress and are regulated by RpoS.…”
Section: Resultsmentioning
confidence: 99%
“…However, many bacteria can survive during oxidative stress conditions, exemplifying the important role of their oxidative stress response systems. Previous studies have reported that RpoS is one of the key regulators of the oxidative stress response in B. pseudomallei .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation